Segurança alimentar e desenvolvimento infantil no bairro Esperança, em Uberlândia - MG - Naves, Agnalda Rodrigues (2010)
Poverty and social inequality increase the risk of diseases, even affecting the infantile development. Through this scenario, Esperança Neighborhood, in Uberlandia City Minas Gerais State, was chosen as the research center for this survey. There was the necessity of improving the nourishment condition of the families of low purchasing power, intervening with a project of safe nourishing with the attempt to improve these families health condition, especially for the children from this community. A collaborative methodology was used in which the mothers learn how to plant and elaborate simple and healthful meals and even to consume easy access and low cost food. In this sense, this study has the objective of presenting the results of the qualitative research, performed from January of 2008 to July of 2010. It was observed that the intervention contributed to the maintenance of the children s nourishment as well as the improvement in their health condition and the prevention of some of the diseases that may attack them in the lack of proper feeding. The study showed that there was an improvement in the health condition of the twenty-three children that were monitored, from which only four had a development below the normal expected. Through this, the study demonstrated the importance of the safe nourishing as a means of collaboration for the families from the community of Esperança Neighborhood Uberlandia, Minas Gerais State.